Perencanaan Instalasi Pengolahan Air Limbah Mal X Kota Bandung - Gita Ayu Rahmawati; Eka Wardhani; Lina Apriyanti (Jurnal Serambi Engineering, 2019)
Waste Water Treatment Plant (WWTP) in the shopping center is planned to cater for its constantly changing concept. The centre was to initially provide electronic services, however, it is currently providing food and beverage services. The changes will affect the amount of wastewater and the characteristics produced. Wastewater discharge is calculated from 80% of the 83.73m  of clean water needed per day. The concentration of the wastewater characteristics obtained for parameters BOD, COD, TSS, oil and fat were 182.67 mg/l, 328.50 mg/l, 255.92 mg/l, 47.93 mg/l respectively. The selection of the processing alternatives is based on the descriptive method which uses a series of selected alternative unit screens, grease traps, equalization tanks, activated sludge, settling tanks and chlorination. The dimensions of the processing unit are calculated based on the selected alternatives. And the land requirements needed to build a WWTP at X Mall amounts to 80m2